10 kVp rule – An anthropomorphic pelvis phantom imaging study using a CR system: impact on image quality and effective dose using AEC and manual mode - Lança, Luís (2013)
Background - Pelvis and hip radiography are consistently found to be amongst the highest contributors to the collective effective dose (E) in all ten DOSE DATAMED countries in Europe, representing 2.8 to 9.4% of total collective dose (S) in the TOP 20 exams list. The level of image quality should provide all the diagnostic information in order not to jeopardise the diagnosis, but being able to provide the needed clinical information with the minimum dose. A recent study suggests further research to determine whether the “10 kVp rule” would have value for a range of examinations using Computed Radiography (CR) systems. As a “rule of thumb” increasing the kVp by 10 whilst halving the mAs is suggested to give a similar perceptual image quality when compared to the original exposure factors. Aims - In light of the 10kVp rule, this study aims to investigate the influence of tube potential (kVp) variation in relation to perceptual image quality and E for pelvis imaging using automatic exposure control (AEC) and non-AEC in a Computed Radiography (CR) system. Research questions - Does the 10kVp rule works for the pelvis in relation to image quality in a CR system? Does the image quality differs when the AEC is used instead of manual mode using the 10kVp rule and how this impacts on E?